Investment screening mechanisms: The trend to control inward foreign investment - Vera Eichenauer; Michael Dorsch; Feicheng Wang (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
In an increasing number of sectors, concerns are rising that foreign firm participation may pose risks to public order. Many developed countries have adopted or extended their investment screening mechanisms to control inward foreign direct investment in strategically important sectors over the last years. This paper documents the development of investment screening in OECD and EU countries and provides the first discussion from an economic perspective. We review existing and propose new explanations for the adoption of investment screening. Our exploratory quantitative analysis suggests that countries with higher levels of technological development and with a stricter regulatory environment for foreign investment are more likely to introduce investment screening. Contrary to the popular wisdom, we do not find evidence that higher Chinese inward investments are associated with the implementation of investment screening.
Keywords: 330; foreign direct investments; national security; investment screening mechanisms